Traditional games for physical fitness in primary school students: A systematic review in Indonesia - Zulnadila, Zulnadila; Suharjana, Suharjana; Arjuna, Fatkurahman; Sriwahyuniati, Christina Fajar; Mappanyukki, Andi Atssam; Rahman, Abdul; Agustina, Dina; Szczepocki, Matthew (Universitas Tanjungpura, 2025)
Background and Study Aim. Physical fitness is a very important factor for students to fight fatigue when doing activities, so that during the learning process at school students can still concentrate on learning. Information on physical fitness in elementary school students is a source of health that really needs to be considered. Therefore, this study aimed to review the scientific literature on physical fitness of primary school children through learning with traditional games in Indonesia.Material and Methods. The search in this study used databases such as ScienceDirect, Scopus, Google Scholar, and PubMed. The search began using the ScienceDirect database, then Scopus, Google Scholar and PubMed. The search strategy included a combination of keyword variations (